The Influence of Transformational Leadership and Organizational Culture on Lecturer Performance through Tacit Knowledge Sharing - Yayah Sutisnawati; Hadi Purnomo; Edi Firdaus (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Higher education institutions play a vital role in developing high-quality human resources, where leadership practices and organizational culture are critical factors influencing knowledge-sharing behavior and lecturer performance. This study aims to examine the effect of transformational leadership and organizational culture on lecturer performance mediated by tacit knowledge sharing in private universities in West Java. A quantitative approach was employed using survey data collected from 100 lecturers through an online questionnaire. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that transformational leadership and organizational culture positively influence tacit knowledge sharing and lecturer performance. Tacit knowledge sharing also directly enhances lecturer performance and partially mediates the relationships between transformational leadership, organizational culture, and lecturer performance. These results highlight the importance of fostering supportive leadership and organizational environments that encourage collaboration, mentoring, and experience sharing to improve lecturer performance. This study contributes to the literature by providing empirical evidence on the role of leadership and organizational culture in promoting tacit knowledge sharing and strengthening academic performance in higher education.